ВОСПИТАНИЕ СОЦИАЛЬНАОЙ ОТВЕТСТВЕННОСТИ БУДУЩИХ МЕНЕДЖЕРОВ - Володько, О.М. (SCIENCE and SOCIETY, 2023)
The article discusses the essence of the social responsibility of management in the form of a rating pyramid and a number of elements in the aggregate. Two factors of the formation of social responsibility are presented: a purposeful educational process and the educational space of the university. The main ways of formation of social responsibility of future managers are investigated: development of ecological culture; formation of moral consciousness; mastering a responsible personnel policy; study of possibilities and forms”; acceptance of responsibility to consumers and partners; study of possible social programs and charity events.